High vs. low oxygen therapy in patients with acute heart failure: HiLo‐HF pilot trial. (17th May 2019) - Sepehrvand, Nariman; Alemayehu, Wendimagegn; Rowe, Brian H.; McAlister, Finlay A.; van Diepen, Sean; Stickland, Michael; Ezekowitz, Justin A.
Abstract: Aims: Most patients with acute heart failure (AHF) are treated with supplemental oxygen during hospitalization. In this study, we investigated the effect of oxygen titrated to high vs. low pulse oximetry targets in patients hospitalized with AHF. Methods and results: In a pilot, open‐label randomized controlled trial (RCT), 50 patients who were admitted with AHF were randomized to either high (≥96%) or low (90–92%) SpO2 targets. Oxygen was manually titrated to the assigned target ranges for 72 h. The primary endpoint was the change in N‐terminal pro‐brain‐type natriuretic peptide (NT‐proBNP) from randomization to 72 h, and secondary endpoints included patient‐reported dyspnoea by visual analogue scale (VAS), patient global assessment (PGA), peak expiratory flow (PEF) within 72 h, and clinical outcomes up to 30 days following hospital discharge. The median age was 73.5 years, and 42% were women. The change in NT‐proBNP was −6963 (−13 345, −1253) pg/mL in the high SpO2 group and −2093 (−5692, −353) pg/mL in the low SpO2 group ( P = 0.46), and the 72 h to baseline NT‐proBNP ratio was similar between groups (0.7 vs. 0.6, P = 0.51). There were no differences between arms in change in dyspnoea VAS ( P = 0.86), PGA ( P = 0.91), PEF ( P = 0.52), in‐hospital mortality (4.0% vs. 8.0%, P = 0.50), or 30 day heart failure readmission rates (20.8% vs. 8.7%, P = 0.22). Conclusions: In this study, no differences were observed in the primary or secondary outcomes for patients randomized to high vs. low SpO2 targets. Further RCTs with larger sample sizes are warranted to determine the efficacy and safety of oxygen therapy in patients with AHF.